DAMPAK TEKANAN PEMBANGUNAN TANPA IZIN PADA PEMANFAATAN RUANG DI KECAMATAN BAOLAN KABUPATEN TOLITOLI - Darise, Ramla Ilham; Anwar, Chairil; Jokolelono, Eko (Katalogis, 2019)
The objective of this research is to find out inappropriate space utilization due to the pressure of develompent is caused of develompent thai is not in accordance with the regional spatial planning and the deviation from the realization and contribution of buildiding construction permits. The results of of the research show that (1) the construction of resident in new district has not all been in accordance with the regional spatial planning. (2)Â Lack of socialization regarding the procedures for arranging construction permits, some people do not understand the way to manage it. (3) There are no deviations from the realization of building construction permits with spatial planning from related agencies.